Penciptaan Karya Seni Instalasi Interaktif Make Noise Not the Art di Sicap Liberte Dakar Senegal - Indrabakti, Moch Hasrul (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
The creation of this artwork employs a practice-based research approach, exploring plastic waste materials and transforming them into interactive installations. The artistic approach in this creation utilizes media art to embody the conceptual ideas. The production process of the artwork is divided into several stages: field observation of everyday objects in the community of Dakar, design, electronic device study, and assembly of the artwork. Additionally, other artistic approaches include the use of readymade and plastic recycling. The result of this creation process is presented in a park near the residential area in Sicap Liberté.